Hippo Signaling-Mediated Mechanotransduction in Cell Movement and Cancer Metastasis - Chang, Yu-Chiuan; Wu, Jhen-Wei; Wang, Chueh-Wen; Jang, Anna C.-C. (Frontiers in Molecular Biosciences, 2020)
The Hippo signaling, an evolutionally conserved kinase cascade, governs cell proliferation, tissue differentiation and organ size control, and promotes tumor growth and cancer metastasis when dysregulated. Unlike conventional signaling pathways driven by ligand-receptor binding to initiate downstream cascades, Hippo core kinases are activated not only by biochemical cues but also by mechanical cues generated from the change of cell shape, cell polarity, cell-cell junction or cell-ECM adhesion. In this review, we focus on recent advances on how mechanical force acts through actin cytoskeleton to regulate the Hippo pathway in cell movement and cancer invasion. We also discuss how the force affects YAP-dependent tissue growth and cell proliferation, and how disturbing such homeostasis contributes to cancer metastasis.